TREN PENELITIAN PENDIDIKAN KEWIRAUSAHAAN DI INDONESIA TAHUN 2021–2025: SYSTEMATIC LITERATURE REVIEW - Wiyoko, Tri; Devita Sari, Nia (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
Entrepreneurship education plays an important role in fostering young entrepreneurs in Indonesia. However, the understanding of trends in research methods and approaches in entrepreneurship education studies remains limited. The objective of this study is to examine trends in research methodologies and approaches employed in entrepreneurship education in Indonesia from 2021 to 2025. Additionally, it seeks to identify the factors that influence students' and university students' entrepreneurial intentions. This study employs a systematic literature review (SLR) approach on articles published in the International Journal of Evaluation and Research in Education (IJERE) from 2021 to 2025. The analysis focuses on research methods, learning strategies, and factors influencing entrepreneurial intent. The findings of the study suggest that quantitative research methodologies predominate (75%) in the examination of the relationship between variables such as locus of control, self-efficacy, entrepreneurial mindset, and family support on entrepreneurial intentions. Qualitative methods are employed to explore the role of parents and society, while R&D methods are developed to build an entrepreneurship education model based on local potential. The factors influencing entrepreneurial intent are multifaceted and include internal factors, education and curriculum, social environment, religious and local cultural values, and technology integration in learning. Consequently, the necessity arises to fortify contextual, holistic, and collaborative entrepreneurship education to cultivate.